Scandcleft Project, Trial 1: Comparison of Speech Outcome in Relation to Timing of Hard Palate Closure in 5-Year-Olds With UCLP. (November 2019) - Willadsen, Elisabeth; Lohmander, Anette; Persson, Christina; Boers, Maria; Kisling-Møller, Mia; Havstam, Christina; Elander, Anna; Andersen, Mikael
Objective: To compare in-depth speech results in Scandcleft Trial 1 as well as reference data from peers without cleft palate (CP). Design: A prospective randomized clinical trial. Setting: A Danish and a Swedish CP center. Participants: 143 of 148 randomized 5-year-olds with unilateral cleft lip and palate. All received lip and velum closure at 4 months, and hard palate closure at 12 months (arm A) or 36 months (arm B). Main Outcome Measures: A composite measure based on velopharyngeal competence (VPC) or velopharyngeal incompetence (VPI), an overall assessment of VPC from connected speech (VPC-Rate), Percentage of Consonants Correct (PCC-score), and consonant errors. Speech therapy visits, average hearing thresholds, and secondary pharyngeal surgeries documented burden of treatment. Results: Across the trial, 61.5% demonstrated VPC and 38.5% VPI. Twenty-two percent of participants achieved age appropriate PCC-scores. There were no statistically significant differences between arms or centers for these measures. In the Danish center, arm B: achieved lower PCC-scores ( P = .01); obtained PCC-scores without s-errors below 79% ( P = .002); produced ≥3 active oral cleft speech characteristics ( P = .004) than arm A. In both centers, arm B attended more speech visits. Conclusions: At age 5, differences between centers and treatment arms were not statistically significant for VPC/VPI, but consonant proficiency differed between treatment arms in the Danish center. Poor speech outcomes were seen for both treatment arms. Variations between centers were observed. As the Swedish center had few participants, intercenter comparisons should be interpreted with caution.